Emotions as pragmatic and epistemic actions - Wilutzky, Wendy (Frontiers in Psychology, 2015)
This paper explores the idea that emotions in social contexts and their intentionality may be conceived of as pragmatic or epistemic actions. That is, emotions are often aimed at achieving certain goals within a social context, so that they resemble pragmatic actions; and in other cases emotions can be plausibly construed as acts of probing the social environment so as to extract or uncover important information, thus complying with the functions of epistemic actions (cf. Kirsh and Maglio, 1994). This view of emotions stands at odds with the wide-held conception that emotions' intentionality can be cashed out in terms of representations of value. On such a position, emotions' intentionality has only a mind-to-world direction of fit while any world-to-mind direction of fit is deemed secondary or is even outrightly denied. However, acknowledging that emotions (qua actions) also have a world-to-mind direction fit has several advantages over the typical rendition of emotions as representations of value, such as accounting for emotions' sensitivity to contextual factors, variations in emotion expression and, importantly, assessing the appropriateness of emotional reactions. To substantiate this claim, several cases of emotions in social contexts are discussed, as the social dimension of emotions highlights that emotions are inherently ways of interacting with one's social environment. In sum, the construal of emotions in social contexts as pragmatic or epistemic actions yields a more fine-grained and accurate understanding of emotions' intentionality and their roles in social contexts than the insistence on a purely mind-to-world direction of fit.